Frontal sinus mucopyelocele with intracranial and intraorbital extension - Gupta, S; Goyal, R; Shahi, M (Nepalese Journal of Ophthalmology, 2011)
This case is related to a 52-year-old lady with proptosis, diplopia and diminution of vision due to a mass lesion in upper medial quadrant of the orbit. CT scan revealed a well defined mass in basi-frontal area with intra-orbital and intracranial extension. On exploring it was found to be mucopyocele of the frontal sinus. Surgical excision was done by external approach. The symptoms and signs resolved completely within a week. Frontal sinus mucopyoceles are benign and curable. Early recognition and management of them is of paramount importance because they can expand and cause local, orbital or intracranial complications. Keywords: Mucocele; mucopyocele; paranasal sinuses; visual loss; proptosis  DOI: 10.3126/nepjoph.v3i1.4287Nepal J Ophthalmol 2011;3(5):91-92